Influence of dentin thickness on intrapulpal temperature under simulated pulpal pressure during Nd:YAG laser irradiation - Santis, L. R. [UNESP]; Silva, T. M. [UNESP]; Haddad, B. A. [UNESP]; Gonçalves, L. L. [UNESP]; Gonçalves, S. E.P. [UNESP] (Springer Nature, 2017)
The aim of this study was to evaluate the effects of dentin thickness and pulpal pressure simulation (PPS) on the variation of intrapulpal temperature (∆T) when submitted to an adhesive technique using laser irradiation. Sixty sound human molars were sectioned and randomly divided into two groups (n = 30): group 1—1 mm of dentin thickness; group 2—2 mm of dentin thickness. Each group was divided into two subgroups (n = 15): subgroup A—absence of PPS; subgroup P—presence of PPS (15 cm H2O), sequentially treated with the following: 37 % phosphoric acid, adhesive system (Adper Single Bond), irradiation with Nd:YAG laser (1064 nm, 10 Hz, 60 s) using 60, 80, and 100 mJ/pulse energy parameters and light-curing (10 s). The ∆T was evaluated during the laser irradiation with a digital thermometer. Data were analyzed by three-way ANOVA and Tukey tests (p < 0.05). Three-way ANOVA revealed no significant differences for dentin thickness (p = 0.6512) on ∆T. PPS significantly reduced ∆T (p = 0.0001). The laser energy parameters (p = 0.0027) indicated that 100 mJ presented with significantly greater ∆T when compared to the groups irradiated with 80 and 60 mJ. Dentin thickness did not affect ∆T. The presence of PPS reduced the mean temperature values. The Nd:YAG laser energy parameters had a negative influence on the variation of temperature in the absence of PPS. In the presence of PPS, there was no risk to the pulp, since this study obtained temperature increases below 5.5 °C for all energy parameters, showing the technical viability for in vivo conditions.
Keywords: Dentin; Intrapulpal pressure; Nd:YAG laser; Temperature